Perencanaan & Penjadwalan Distribusi Pakaian Jadi dengan Metode Distribution Resource Planning - Syarif Hidayat; Nunung Nurhasanah; Anela Septieni Zulkifli (Jurnal Optimasi Sistem Industri, 2013)
The tight competition in the business world nowadays, especially after the signing of AFTA and ACFTA agreements calls for an increased competitiveness of domestic industries especially the garment industries. High quality products, competitive prices and the availability of products in the ever changing fashion market are the key factors to win the competition.Distribution is one of the important activities as it is directly related to fulfilling customer needs. Right products must be available in the right quantity and right condition and at the right time. Product availability in the market should be strong to prevent lost sales. However, a high service level means high inventory costs. Companies need tool to manage their inventory.This research proposes the planning and scheduling of distribution at XYZ using the Distribution Resource Planning (DRP) for product X102 for five selected distributors (Surabaya, Bogor, Pekalongan, Sidoarjo and Probolinggo) using the Exponential Comparison Method (ECM). The DRP results show that XYZ must issue production orders in the 3rd, 5th, 7th periods for X102 in the amount of 150 units. In addition to the DRP, to help the company controls the inventory level, the researchers developed a model of Excess Stock Management system using Dev C++.Keywords: Garment industry, Exponential Comparison Method, Distribution Resource Planning